DAKWAH THROUGH INTERNET: CHALLENGES AND OPPORTUNITIES FOR ISLAMIC PREACHERS IN INDONESIA - Arifuddin, Arifuddin (UIN Ar-Raniry, 2016)
The development of information technology (IT), particularly the internet, has benefited people throughout the world in many fields. Considering the advantages offered by the internet, the da’i (Islamic preachers) may utilize such product of IT advancement for disseminating Islamic messages and knowledge (dakwah). This literature review explores the challenges and opportunities of the internet utilization for such religious purpose, by extracting views and research findings from a range of publications, including books and journal articles from several databases. It found that the internet can be utilized as contemporary media for dakwah endeavor as it has many advantages in terms of efficiency, accessibility, scoping, and openness. Some recent global issues including Islamophobia, extremist activities including Islam-related terrorism, and gender equity are seen as challenges to the contemporary Islam. On one hand, these concerns may challenge the use of the internet for dakwah practice, but on the other hand, such issues has opened opportunities for da’i to remedy the situation through valid views described in many forms of dakwah in the internet, educating mad’u for better understanding of Islam. It is further recommended that da’i in Indonesia can consider the internet as media for da’wah. Further research is essential whether to explore the da’i’ interests and acceptance in the use of internet for dakwah as well as the social impacts of such approach.Keywords: